Heterogeneous genetic diversity pattern in Plasmodium vivax genes encoding merozoite surface proteins (MSP) -7E, -7F and -7L (2014)
Background: The msp-7 gene has become differentially expanded in the Plasmodium genus; Plasmodium vivax has the highest copy number of this gene, several of which encode antigenic proteins in merozoites. Methods: DNA sequences from thirty-six Colombian clinical isolates from P. vivax (pv) msp-7E, -7F and -7L genes were analysed for characterizing and studying the genetic diversity of these pvmsp-7 members which are expressed during the intra-erythrocyte stage; natural selection signals producing the variation pattern so observed were evaluated. Results: The pvmsp-7E gene was highly polymorphic compared to pvmsp-7F and pvmsp-7L which were seen to have limited genetic diversity; pvmsp-7E polymorphism was seen to have been maintained by different types of positive selection. Even though these copies seemed to be species-specific duplications, a search in the Plasmodium cynomolgi genome (P. vivax sister taxon) showed that both species shared the whole msp-7 repertoire. This led to exploring the long-term effect of natural selection by comparing the orthologous sequences which led to finding signatures for lineage-specific positive selection. Conclusions: The results confirmed that the P. vivax msp-7 family has a heterogeneous genetic diversity pattern; some members are highly conserved whilst others are highly diverse. The results suggested that the 3′-end of these genes encode MSP-7 proteins' functional region whilst the central region of pvmsp-7E has evolved rapidly. The lineage-specific positive selection signals found suggested that mutations occurring in msp-7s genes during host switch may have succeeded in adapting the ancestral P. vivax parasite population to humans. © 2014 Garzón-Ospina et al.